Pedagogia das tecnologias de informação e comunicação (TIC) : outros tempos, outros espaços, outros saberes necessários à prática docente - Oliveira, Eliane Vasconcelos (2017)
The current society called "information society" has as a characteristic the communication at high speed. Thus, with the expansion of Information and Communication Technologies (ICT), the way the human being behaves before the world and the other has been altered. In this society, the school environment divides space with computers, internet, tablet, cell phones, etc. Faced with this reality, educators are challenged to rethink their knowledge and teaching methodologies, as well as to review their teaching practices, in order to enable the student to build knowledge in a playful, interactive and critical way. In this perspective, the aim of this research was to understand how teachers of Natural Sciences and Mathematics use the technologies, in High School. Collaborated with the study: six teachers of science teaching and mathematics, thirteen students of the third year of high school and eight specialists in education In an attempt to support this study, we sought support in authors such as Castells, (2006); Freire, (2011); Kenski, (2001, 2003 and 2013); Libâneo, (2004 and 2015); Richardson, (2012); Tardif, (2010) and others that approach the theme. It was decided by qualitative approach, such as a case study, using observation techniques, questionnaire and guided interview. In order to study and interpret the information, we opted for the Bardin content analysis (2011, p.50), considering that this technical of analyzing communications "aims at the knowledge of variables ... through mechanisms of deduction based on indicators reconstructed from a sample of particular messages ". Thus, it was possible to perceive that: there are teachers who remain oblivious to this social reality permeated by ICT; technologies have entered the school environment, teachers and students are engaging in the use of ICT for pedagogical purposes; but it was also visible the permanence of "old practices" that do not reality fit. Against this data, we outline a Technology Pedagogy with the perspective of contributing to significant changes occurring.